Does visual perception have more impact for effective learning in dental anatomy (Tooth carving practical session)? - Ko, Bo Bo @ Bo Bo; Oo, Mon Mon Tin (Myanmar Dental Association, 2013)
Tooth carving practical sessions usually in wax are indispensible for the achievement of course objectives in teaching Dental anatomy to initiate and develop the psychomotor skills of the students which are really essential in forthcoming clinical years. This study was carried out in two consecutive first year dental batches, at school of dentistry, International Islamic University Malaysia and all together 90 students participated in it. The study design was a randomized controlled single blind cross-sectional interventional study. The students were randomly divided into two groups based on equal gender ratio and they were assigned to do the wax tooth carving of 11(permanent maxillary right central incisor). One group received conventional class room instructions from instruments handling to detailed carving procedure. The other group received verbal instructions for instruments handling and detailed carving procedure was displayed by a video clip developed by the Oral Biology unit. Both groups were allowed to do the carving for two hours exactly. The student performance was evaluated from the finished carved wax tooth models by giving the grades based on the resemblance to that particular natural tooth. Grading was scored by the expert and she was blinded that which group received video clip display on tooth carving demonstration. Better students’ performance for general resemblance was found in the group where a video clip was displayed (p<0.05). However, for the particular surfaces, the grades achieved for the mesial and distal surfaces were statistically significant (p<0.05) only. Findings for the rest of the surfaces (labial, lingual, incisal) were not statistically significant (p>0.05).